Plasma lactate versus c-reactive protein as prognositic indicator in urosepsis - Prilistiyo, Dwimantoro Iman; Santoso, A; Anniwati, L; Pudjirahardjo, W J (Folia Medica Indonesiana, 2017)
Urosepsis occurs in 20-30 % of septic case. Early diagnosis were undoubtfully important to improve the results of sepsis management. Bacteriological confirmation may be difficult to obtain and negative cultures do not exclude the presence of infection. Increased understanding of inflammatory cascade mechanisms provided several indicator of infection and prognosis. Lactate measurement in patients with infection and possibly severe sepsis to help identify patients at high risk of death in order to apply aggressively therapy. Elevation in serum C-reactive protein (CRP) is also associated with an increasing risk of death in patients with infection. This study was to determine the plasma lactate and CRP levels of patients with urosepsis as a prognostic indicator. This is an analytic observational study to compare the correlation and significance of plasma lactate and CRP with prognosis of urosepsis. Each subject was measured for plasma lactate and serum CRP at time of admission. All subjects were managed according to standard protocol. At the 14th day of treatment, patients were evaluated with a clinical severity score. The outcome was classified as follows: 1=good condition/improved, 2=morbid/worsened and 3=death. The statistical analysis used Spearman's rho test, Ï<0.05 was considerated to indicate significance. We enrolled 25 subjects with urosepsis. 14 patients who were septic, nine patients had severe sepsis and 2 patients had septic shock. Mean plasma lactate level in patients based on outcome (improved/worsened/death) was 2.08 mmol/L; 4.16 mmol/L and 5.27 mmol/L. The mean value of CRP was 13.41 mg/L; 22.28 mg/L and 24.62 mg/L. These were statistically significant (p 0.008 vs 0.016) in determining the outcome of the urosepsis patient. The coefficient correlation is better with plasma lactate than CRP (0.517 vs 0.475). In conclusion, the measurement of plasma lactate and CRP level can be used as a prognostic marker for the outcome of patient with urosepsis. Plasma lactate showed higher correlation with outcome of urosepsis than CRP.